Effect of High-Humidity Hot Air Impingement Steaming on Cistanche deserticola Slices: Drying Characteristics, Weight Loss, Microstructure, Color, and Active Components - Ai, Ziping; Lin, Yawen; Xie, Yongkang; Mowafy, Samir; Zhang, Yue; Li, Mengjia; Liu, Yanhong (Frontiers in Nutrition, 2022)
Cistanche deserticola is one of the most precious herbal medicines and is widely used in the pharmaceutical and healthy food industries. Steaming is an important step prior to drying in the processing of Cistanche deserticola. This research investigated the effects of high-humidity hot air impingement steaming (HHAIS) parameters such as temperature, time, and relative humidity (RH) on drying characteristics, weight loss, color, microstructure, and active components of Cistanche deserticola slices. The results showed that the steaming process caused a weight loss of Cistanche deserticola; however, increasing the RH reduced the weight loss. Starch gelatinization observed from the microstructure of the steamed samples explained their long drying time. Page model can well fit the drying process with a high R2 (＞0.956) under the drying conditions of 60 °C & 6 m/s. Steaming increased phenylethanoid glycosides (PhGs) content, and the highest content was obtained at 95 °C and 60% RH for 20 min, 75 °C and 70% RH for 20 min, and 75 °C and 60% RH for 30 min. Steamed samples showed an oil black color appearance color. When the color difference (ΔE) values were in the range of 16.79-20.12, the contents of echinacoside and acteoside reached the maximum. Steaming at 95 °C and 60% RH for 20 min, 75 °C and 70% RH for 20 min, and 75 °C and 60% RH for 30 min are the optimum process conditions. The results from this work provide an innovative steaming technology and suitable processing parameters for producing Cistanche deserticola decoction pieces with high quality, which will broaden its potential application in the functional health food industry.